The Role of Teachers and Structural Barriers in Adolescent Anemia Education in Surabaya Schools - Feriyanti, Alma; Nurmala, Ira; Widati, Sri; Muthmainnah, Muthmainnah; Notobroto, Hari Basuki (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Anemia in adolescents, particularly young women, remains a significant public health concern in Indonesia, with low adherence to iron supplementation being a key contributing factor. While previous interventions have focused primarily on individual compliance, the role of teachers as health educators in schools is often overlooked. This study aimed to analyze the determinants of teachers’ intention to provide health education on anemia prevention in Surabaya high schools.Method: A cross-sectional survey was conducted among 119 high school and vocational school teachers within the working area of Tanah Kali Kedinding Health Center, selected through simple random sampling from a total population of 170 teachers. Data were collected using structured questionnaires and analyzed using multiple logistic regressions to assess the influence of attitudes, subjective norms, and perceived behavioral control on teachers' intention to deliver health education.Result: The analysis indicated that teacher' attitudes, subjective norms, and perceived behavioral control did not significantly influence their intention to deliver health education on iron supplementation. This indicates that structural and institutional factors, rather than individual psychological characteristics, primarily influence teachers' involvement in health education delivery.of the risks of e cigarettes. Efforts to enhance adolescent anemia prevention should address structural barriers within the educational system. Policy support from schools and educational authorities is critical to institutionalizing health education as part of the teachers' formal responsibilities.